Papules arising after radiotherapy for rhabdomyosarcoma - Brunasso, Alexandra Maria Giovanna (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2009)
Radiation therapy, even at low doses, can induce a wide spectrum of vascular skin proliferations ranging from nonmalignant ones, such as benign lymphangiomatous papules (BLAP), to frankly malignant pathologies, such as angiosarcoma. We describe a 50-year-old Caucasian woman with a past history ofuterine rhabdomyosarcoma, treated 22 years prior with surgical excision, chemotherapy, and radiotherapy. She presented with a few skin-colored papules and a clear discharge located in the previously irradiated area (right inguinal region). Histopathology showed a proliferation of irregular, interanastomosing vascular channels, thin walled and lined by prominent endothelial cells with focally hobnail features. Cytological atypia of endothelial cells, mitotic figures, hemorrhagic areas, and necrosis were not observed. The endothelial cells expressed D2-40 and CD31. A diagnosis of BLAP following radiotherapy for uterine rhabdomyosarcoma was made. The patient wastreated with complete excision using electrodessication. At the 20-month follow-up visit the patient was still free of recurrence.
Keywords: Adverse Effects; Etiology; Kožne novotvorbe; Limfangiom; Lymphangioma; Maternica, novotvorbe; Neoplasms, Radiation-Induced; Novotvorbe povzročene z obsevanjem; Pathology; Rabdomiosarkom; Radioterapija; Radiotherapy; Rhabdomyosarcoma; Skin Neoplasms; Surgery; Uterine Neoplasms